Leadership Styles and Technical Knowledge of Public Employees in Nueva Ecija - Catingco-Guiang, Mary Kesia; Cabute, Zenaida Corsino; Dela Cruz, John Michael M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research study described and examined the relationship of leadership styles and acquired technical knowledge on project im-plementation practices among division chiefs and department heads in the provincial government. The study utilized Mixed Method of Research. Further, there were 64 respondents partici-pated in the study. Results showed that majority of the respond-ents manifested democratic aspects of leadership. Also, there was a significant difference on the level of leadership styles of the re-spondents as to democratic aspects was noted when grouped ac-cording to dimensions, a significant difference on the level of lead-ership styles of the respondents. Findings further revealed that democratic aspects was positively correlated with Acquired Tech-nical Knowledge on Project Implementation in terms of Activities/ projects/programs implemented, Leadership Styles on Project Im-plementation Practices as to delegative aspect was positively cor-related with Acquired Technical Knowledge on Project Implemen-tation in terms of Activities/ projects/programs implemented. Hence, Leadership Styles on Project Implementation Practices as to delegative aspect was negatively correlated with Acquired Technical Knowledge on Project Implementation in terms of transparency aspect. It was also found out that overlapping work-loads and complex documentary preparations and submission of reports were the issues and problems encountered by the re-spondents. The study recommended the implementation of inter-vention program to enhance the Technical Knowledge on Project Implementation Practices.